An epidemiological data of oral health status and treatment needs of rural population of Nellore district, Andhra Pradesh, India - Deepthi Athuluru; V Chandrasekhara Reddy; K M Sudhir; R.V. S Krishna Kumar; Srinivasulu Gomasani; Sreenivas Nagarakanti (Wolters Kluwer Medknow Publications, 2016)
Introduction: As India is the second highest populated country and approximately 72% of this population live in rural areas, an attempt has been made to assess the prevalence of oral diseases in rural areas. Aim: To assess the prevalence of oral diseases in 5, 12, 35-44, and 65-74 years old population in rural areas of Nellore district, Andhra Pradesh, India. Materials and Methods: A cross-sectional survey was carried out using multistage cluster sampling methodology, and random samples of participants were selected. Data were collected on sociodemographic details, oral hygiene practices, and clinical oral health data collected according to the World Health Organization methodology criteria and simplified oral hygiene index. Data were analyzed using Chi-square test and linear and logistic regression. Results: Among 35-44 and 65-74 years age group, 54.1% and 42.2% of the population showed poor oral hygiene status. At age 12 years, 51% of children had caries; mean decayed, missing, filled teeth was 3.24 in 35-44 years and 12.01 in 65-74 years. Extraction was the most required treatment (52.1%) for older people, pulp care therapy for 12 years old (16.5%) and 35-44 years old (23.2%). Community periodontal index score 2 was dominant in 12 years old (30.5%) and 35-44 years old (54.6%) and score 3 in 65-74 years (46.9%) population. Definite malocclusion was seen in 18% of 12 years old population. All the independent variables were related to caries and periodontal status (P < 0.05). Conclusion: The study population was characterized by high prevalence of dental caries, periodontal diseases, and poor oral hygiene status, and age of the population is the most associated factor for dental caries and periodontal diseases.